Rapid detection of antibiotic resistance in Burkholderia pseudomallei using MALDI-TOF mass spectrometry - Nut Nithimongkolchai; Yothin Hinwan; Kanwara Trisakul; Lumyai Wonglakorn; Ploenchan Chetchotisakd; Auttawit Sirichoat; Arnone Nithichanon; Sorujsiri Chareonsudjai; Pisit Chareonsudjai; Jody Phelan; Taane G. Clark; Kiatichai Faksri (Scientific Reports)
Abstract Antibiotic resistance in Burkholderia pseudomallei (Bp) is a growing public health concern requiring urgent attention. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has emerged as a rapid bacterial identification tool with potential for future diagnostic applications. This study investigates differences in MALDI-TOF spectra of antibiotic-resistant Bp strains from northeastern Thailand without any pretreatment steps. A total of 300 Bp isolates were tested for minimum inhibitory concentration (MIC) values against five antibiotics: ceftazidime, meropenem, imipenem, co-amoxiclav, and co-trimoxazole. MALDI-TOF spectra were obtained using the direct colony method and analysed for correlations with antibiotic resistance patterns. Thirteen isolates exhibited resistance based on CLSI breakpoints, with most showing low-level MICs across all tested antibiotics. MALDI-TOF MS analysis revealed clustering patterns associated with resistance. A decision tree algorithm identified ten significant peaks that effectively distinguished resistant isolates. This study highlights MALDI-TOF MS as a rapid and reliable tool for detecting antibiotic resistance, offering timely results to support treatment decisions and streamline microbiology workflows.